On the regularity of solutions of quasilinear Poisson equations - Gutlyanskiĭ, V.Ya.; Nesmelova, O.V.; Ryazanov, V.I. (Доповіді НАН України, 2018)
We study the Dirichlet problem for quasilinear partial differential equations of the form Δu(z) = h(z)f(u(z)) in the
unit disk D ⊂ C with continuous boundary data. Here, the function h : D→R belongs to the class L^p(D), p > 1, and
the continuous function f : R→R is assumed to have the nondecreasing |f| of |t| and such that f(t) / t →0 as
t →∞. We prove the existence of a continuous solution u of the problem in the Sobolev class W^2,p loc (D). Moreover,
we show that if p > 2 , then u∈ C^1,α loc (D) with α = (p − 2)/p. Вивчається задача Діріхле для квазілінійних диференціальних рівнянь у частинних похідних виду
Δu(z) = h(z)f(u(z)) в одиничному колі D ⊂ C з неперервними граничними умовами. Тут функція h :D→R
належить класу Lp(D), p > 1, і неперервна функція f : R→R припускається такою, що її | f | як функція
від | t | є неспадною і такою, що f (t) / t →0 при t →∞ . Доводиться існування неперервного розв’язку
u даної проблеми в класі Соболєва W^2,p loc (D). Більш того, показано, що якщо p > 2 , то C^1,α loc (D) з
α = (p − 2)/p. Изучается задача Дирихле для квазилинейных дифференциальных уравнений в частных производных
вида Δu(z) = h(z)f(u(z)) в единичном круге D ⊂ C с непрерывными граничными условиями. Здесь функция h :D→R принадлежит классу Lp(D), p > 1, и непрерывная функция f : R→R предполагается такой,
что ее | f | как функция от | t | является неубывающей и такой, что f (t) / t →0 при t →∞. Доказывается
существование непрерывного решения u рассматриваемой проблемы в классе Соболева W^2,p loc (D). Более
того, показано, что если p > 2 , то C^1,α loc (D) с α = (p − 2)/p.